Addressing MSMEs Customer Complaints in Indonesia’s Digital Economy: Insights from Sharia and Consumer Protection Law - Astuti, Miguna; Mardiatmi, Anastasia Bernadin Dwi; Sari, Afrina; Dewi, Fransisca Iriani Roesmala (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study examines MSME customer segmentation based on complaint behavior and the influence of Recency, Frequency, and Monetary (RFM) metrics. It integrates consumer protection law in Indonesia and sharia principles to address customer complaints. Using a mixed-method approach, quantitative analysis of RFM data and descriptive segmentation were combined with qualitative normative legal analysis. Data collection involved online and offline surveys in the Jabodetabek area using structured questionnaires covering RFM metrics, demographics, and complaint patterns. Findings reveal that 35.57% of MSMEs 4.0 customers belong to the